Common and Specific Mechanisms of Desiccation Tolerance in Two Gesneriaceae Resurrection Plants. Multiomics Evidences - Liu, Jie; Moyankova, Daniela; Djilianov, Dimitar; Deng, Xin (Frontiers in Plant Science, 2019)
Environmental stress, especially water deficiency, seriously limits plant distribution and crop production worldwide. A small group of vascular angiosperm plants termed “resurrection plants”, possess desiccation tolerance (DT) to withstand dehydration and to recover fully upon rehydration. In recent years, with the rapid development of life science in plants different omics technologies have been widely applied in resurrection plants to study DT. Boea hygrometrica is native in East and Southeast Asia, and Haberlea rhodopensis is endemic to the Balkans in Europe. They are both resurrection pants from Gesneriaceae family. This paper reviews recent advances in transcriptome and metabolome, and discusses the differences and similarities of DT features between both species. Finally, we believe we provide novel insights into understanding the mechanisms underlying the acquisition and evolution of desiccation tolerance of the resurrection plants that could substantially contribute to develop new approaches for agriculture to overcome water deficiency in future.